2019
DOI: 10.1038/s41392-019-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting growth hormone function: strategies and therapeutic applications

Abstract: Human growth hormone (GH) is a classical pituitary endocrine hormone that is essential for normal postnatal growth and has pleiotropic effects across multiple physiological systems. GH is also expressed in extrapituitary tissues and has localized autocrine/paracrine effects at these sites. In adults, hypersecretion of GH causes acromegaly, and strategies that block the release of GH or that inhibit GH receptor (GHR) activation are the primary forms of medical therapy for this disease. Overproduction of GH has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 150 publications
4
89
0
5
Order By: Relevance
“…I t is known that growth hormone (GH) exerts several diverse actions in addition to somatic growth stimulation, which involve metabolic regulation as well as modulation of immune, reproductive, and neural functions, including behavior, among others. 1,2 Regarding the neural effects of GH, it has been shown recently that its clinical application has revealed promising results as a treatment for stroke, spinal cord injury, brain trauma, and neurodegenerative diseases. 3,4 Also, important neurotrophic actions of GH in the neuroretina are related with the modulation of developmental apoptosis and neuroprotection, 5,6 because it has been observed that exogenous GH administration protects against experimental excitotoxic damage.…”
mentioning
confidence: 99%
“…I t is known that growth hormone (GH) exerts several diverse actions in addition to somatic growth stimulation, which involve metabolic regulation as well as modulation of immune, reproductive, and neural functions, including behavior, among others. 1,2 Regarding the neural effects of GH, it has been shown recently that its clinical application has revealed promising results as a treatment for stroke, spinal cord injury, brain trauma, and neurodegenerative diseases. 3,4 Also, important neurotrophic actions of GH in the neuroretina are related with the modulation of developmental apoptosis and neuroprotection, 5,6 because it has been observed that exogenous GH administration protects against experimental excitotoxic damage.…”
mentioning
confidence: 99%
“…Human GH is a classical pituitary endocrine hormone essential for normal postnatal growth that has pleiotropic effects across multiple physiological systems, while its overproduction has been linked to cancer. The hormone is also expressed in extra-pituitary tissues and shows localized autocrine/paracrine effects at those sites [10]. Although the theoretical concern of increased tumor growth for patients taking GH has been addressed by numerous studies, a meta-analysis by Shen et al included 4 studies and actually found that GH was associated with a decreased risk of craniopharyngioma recurrence in adults [11].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, GH is secreted from the anterior pituitary lobe into the circulation and transported primarily to the liver where it binds the GHR [8]. Ligand binding to the transmembrane homodimeric receptor complex induces a conformational change and concomitant phosphorylation of the tyrosine kinase, Janus kinase 2 (JAK2), which in turn lead to activation of downstream signal transducer and activator of transcription 1 (STAT1), STAT3 and STAT5 [8,9]. Ligand binding and GHR activation also results in direct activation of Src family kinases (SFKs), independent of JAK2, and leads to activation of mitogen-activated protein (MAP) kinase.…”
Section: Introductionmentioning
confidence: 99%
“…The STAT transcriptional regulators dimerize and bind to GH-responsive elements in promoter regions of target genes and activate transcription. STAT5 is the major mediator and predominant transcription factor that mediates GH-induced cell proliferation through the upregulation of IGF-1 [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation